2012
DOI: 10.1007/s11062-012-9257-1
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Auditory Cognitive Evoked Potentials in Musicians

Abstract: We measured characteristics of evoked potentials, EPs, developing after presentation of significant tonal acoustic stimuli in subjects systematically engaged in music training (n = 7) and those having no corresponding experience (n = 10). The peak latencies of the P3 component in the left hemisphere of musicians were significantly shorter than those in non-musicians (on average, 279.9 and 310.2 msec, respectively). Musicians demonstrated no interhemisphere differences of the latencies of components N2, P3, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“… Okhrei et al. (2012) investigated P3 in 7 musicians and 10 non-musicians using tonal stimuli which showed that the peak latency of P3 component in the left hemisphere was significantly shorter in musicians compared to non-musicians.…”
Section: Roadmap Of Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“… Okhrei et al. (2012) investigated P3 in 7 musicians and 10 non-musicians using tonal stimuli which showed that the peak latency of P3 component in the left hemisphere was significantly shorter in musicians compared to non-musicians.…”
Section: Roadmap Of Reviewmentioning
confidence: 99%
“…Music training contributes to the development of cognitive and linguistic abilities with increment in neuroplasticity along cortical and sub-cortical pathways of the auditory system as revealed by various electrophysiological studies ( Bidelman and Krishnan, 2010 , Musacchia et al., 2008 , Okhrei et al., 2012 , Nikjeh et al., 2009 , Polat and Ataş, 2014 ). Music requires a wide range of processing mechanism which consists of encoding of sounds at a higher cognitive level involving memory, sequencing and learning.…”
Section: Introductionmentioning
confidence: 99%
“…Зокрема, установлено, що музиканти демонструють менш виражену функціональну асиметрію під час бісекційного тесту [28] та не мають міжпівкульних відмінностей у латентності компонента N1 під час реєстрації зорових викликаних потенціалів [29], у той час як у групі немузикантів компонент N1 з'являвся раніше в лівій півкулі. Крім того, у нашому попередньому дослідженні показано, що в музикантів відсутня міжпівкульна різниця в часі появи компонентів когнітивних викликаних потенціалів (N2, P3, N3), тоді як у немузикантів ці компоненти з'являлися раніше в лівій півкулі [30].…”
Section: рис 2 латентні періоди реакцій правої й лівої рук музикантunclassified